Siri indeks al-Quran: Surah An-Nas (SIASA) / Rose Zaimi Mohamed Zaid - Rose Zaimi , Mohamed Zaid (2002)
Siri index Al-Quran: Surah An-Nas (SIASA) is an interactive multimedia software which function is to provide an indexing of the Surah An-Nas by conducting search using user selection. Not only that, SIASA will also cater other functions such as display an introduction to the Al-Quran and the surah An-Nas, display the surah An-Nas in its Arabic transcript, provide a few translation and tafseer of the surah An-Nas and provide recitation of the surah An-Nasby a few Qari. This report will give an overview on steps that have been taken into measure to ensure the success of this project. This report is divided into five parts. The first part is an introduction to the project. This section will include topics such as project definition, project objectives, scope of project, target users and project schedule. The second part of this report is the literature review. In this section, a few relevant topics to this project were picked out to be analyze to enhance knowledge on what have been done by other people. Methodologies that have been adopted to develop this project will be covered in the third part of this report. The fourth part of this report is the system analysis. This section will consist an introduction, task analysis, functional requirements and external interface requirements. The fifth part is the system design. Here, the system functionalities, database design and user interface design will be discussed. The last three parts will discuss on techniques and approach that will be adopted to important, test and evaluate the system.